Filsafat Pendidikan Islam: Konstruksi Tipologis dalam Pengembangan Kurikulum - Moch Tolchah (Universitas Darussalam Gontor, 2015)
Islamic education philosophy is essentially a concept to think about education based on Islamic teachings. Islamic education philosophy speaking about nature of Muslim’s ability to be fostered, developed, and be guided into human being whose entire personality imbued with Islamic teachings, cause the complexity of educational problems and so complicated to interpret philosophy, so it needs a simplification. Typology in all aspects of thinking has implications for the “simplification” to a variety of complex issues. A discourse should evolve and expand to be understood in simple after typology. It was certainly no exception to typology philosophical discourse of Islamic education in Indonesia. Curriculum development at this time cannot be separated from the basic ideas are developed from educational philosophy, such as Essentialism, Perennialism, Progressivism, Existentialism, Reconstructionism, and others. This article tries to make typology of philosophical discourse towards the development of Islamic education in Indonesia through literature and its implications for curriculum development in Indonesia. So that the educational philosophy which developed in Indonesia can be seen in their entirety and as simple as possible. Thus, the simplification of the complex things can be realized. On the other side, apprehensive about the release of the current curriculum with a philosophical foundation at least be minimized.